Construct and validation a physical fitness test for students applying for admission to the College of Physical Education and Sports Sciences - Muhammad, Farah; Ahmed, Zahra (Journal of Physical Education, 2023)
The aim of the research is to build and standardize the physical fitness measurement test for students applying to the Faculty of physical education and Sports Sciences /University of Baghdad and finding standard levels and grades for them. The researchers used the descriptive method in the survey method to suit the research problem, and the research community was represented by the students of the first stage at the Faculty of physical education and Sports Sciences, University of Baghdad for the academic year 2022-2032, numbering (351) students. As for the research sample, it was represented by (280) students after excluding cases of repetition, postponement and teachers. The researchers concluded that the physical fitness measurement test for students applying for admission to the Faculty of physical education and Sports Sciences, University of Baghdad, achieved the purpose for which it was designed and reached the development of grades and standard levels for the physical fitness test for students applying for admission to the Faculty of physical education and Sports Sciences, University of Baghdad.The two researchers recommended the adoption of the physical fitness Measurement Test prepared by the two researchers at the Faculty of physical education and Sports Sciences, University of Baghdad.